PELANGGARAN DAN KECELAKAAN LALULINTAS DIKALANGAN REMAJA KOTA PADANG - wahyu pramono; Dwiyanti Hanandini (Jurnal Administrasi Publik dan Pemerintahan, 2022)
Indonesia ranked to five the number of deaths most because of traffic accident. Is a traffic accident motor vehicles most compared with adults. Motorcycle become the first rank of motor vehicles accident. Traffic accidents begins with a mistake individuals because violate traffic rules. This paper assess the a road traffic accident among teenagers and factors. Research conducted using the quantitative approach with a middle of the data. Respondents research are teenagers users motorcycle in high school. Samples taken to technique the sample intentional. The number of samples from 100 people. Data analyzed using statistic packed program for social sciences. Research conducted in SMAN 3 Padang city. The results of the study showed that although of teenagers on the traffic regulation is good but behavior of young people in traffic there are still many who flouted the rules. No consistency of knowledge in regard to the regulation traffic with his behavior traffic. The accident happened young people in traffic caused by a violation of traffic signals. Placement traffic signals in strategic locations, crowded, a lot of activity encourage road users violations. More action forcefully from police are required so that the deviation (offense traffic) teenagers not increase